Outbound open innovation policy for exploitation of intellectual creation, design and creativity in Malaysian public universities / Haswira Nor Mohamad Hashim ... [et al.] - Mohamad Hashim, Haswira Nor; Muhamad Khair, Muhamad Helmi; Mahmood, Anida; Mohd Zakuan, Zeti Zuryani (Universiti Teknologi MARA, 2020)
The objective of the research is to explore the aim, application and strategy perceived as important in the development of an outbound open innovation policy for exploitation of intellectual creation, design and creativity in Malaysian public universities (MPUs). Under existing intellectual property, innovation and commercialization policies, a large portion of intellectual design, creation and creativity in MPUs remain unexploited. Hence, the need to develop a new set of aim, application and strategy to promote the exploitation of intellectual design, creation and creativity in MPUs. The research conducts a survey involving respondents representing the Technology Licensing Office of 15 MPUs. The research also analysed outbound open innovation policies from five universities in Australia, UK, US and South Africa. These policies provide the basis in the development of the survey instrument of the research. The survey instrument contains nine items outlining the aim, application and strategy for exploitation of an outbound open innovation policy. The survey findings indicate that eight of the items are perceived as important for the development of the policy. The findings of the survey provide a beneficial input for the development of an outbound open innovation policy for exploitation of intellectual design, creation and creativity in MPU.